EFEKTIVITAS PEMBERIAN REBUSAN DAUN KERSEN DAN DAUN SIRIH MERAH TERHADAP PENURUNAN KADAR GULA DARAH PADA PASIEN DM TIPE II DI WILAYAH KERJA PUSKESMAS SIMPANG TIGA KOTA PEKANBARU - Anita Syarifah; Shinta Dewi Kasih Brata; Muhammad Irwan (Ensiklopedia of Journal, 2023)
Changes in lifestyle patterns and unhealthy dietary patterns such as consuming a lot of foods that are high in glucose so that they cannot control blood sugar levels which can cause Diabetes Mellitus. The treatment method of Diabetes Mellitus are used, namely pharmacology and non-pharmacology. One way to overcome non-pharmacology in Type 2 DM is to use boiled water of kersen and piper ornatum. The purpose of this study was to determine the efectivity of kersen and piper ornatum boiled water o decreas blood glucose level of non insulin dependent daibetes mellius patient at simpang tiga public health center 2022. This study used a quasy-experimental design with a pre-post test group design. Data collection was carried out using observation. The sample was determined by purposive sampling method of 30 respondents with 15 intervention groups of kersen boiled water  and 15 intervention groups of piper ornatum boiled water. The analysis was carried out with univariate analysis and bivariate analysis using the Mann-Whitney T test. Statistical test results obtained p value of 0.001<0.005, it can be concluded that there are differences in the efectivity of kersen and piper ornatum boiled water o decreas blood glucose level of non insulin dependent daibetes mellius. It is recommended that the public can apply therapy to kersen boiled water and piper ornatum boiled water to overcome Type II DM.